Time for Outrage: Indignez-Vous! - Hessel S.; Duvert Marion (New York Boston Twelve, 2011)
This controversial, impassioned call-to-arms for a return to the ideals that fueled the French Resistance has sold millions of copies worldwide since its publication in France in October 2010. Rejecting the dictatorship of world financial markets and defending the social values of modern democracy, 93-old Stephane Hessel -- Resistance leader, concentration camp survivor, and former UN speechwriter -- reminds us that life and liberty must still be fought for, and urges us to reclaim those essential rights we have permitted our governments to erode since the end of World War II.
Keywords: 32